Fintech for good: Governance mechanisms for sustainable development - Sep Pashang; Olaf Weber (Centre for International Governance Innovation (CIGI), 2021)
Financial technology (fintech) for good can help to achieve sustainable development through environmental, social and governance investing, and through financial inclusion initiatives to address the needs of underbanked and unbanked individuals. Although the COVID-19 pandemic has necessitated greater dependence on digital banking technologies, the lack of cohesive governance and regulatory mechanisms around fintech in Canada and abroad is an obstacle toward achieving the UN Sustainable Development Goals. The authors of this paper argue that better governance and regulatory frameworks are needed to minimize the risks associated with fintech for good while maximizing its benefits.
Keywords: 330; Financial Technology; Financial Inclusion; Sustainable Development; Sustainable Investment; Sustainable Development Goals; Finanztechnologie; Finanzielle Inklusion; Nachhaltige Entwicklung; Nachhaltige Kapitalanlage; Sustainable Development Goals